Business–nonprofit hybrid organizing: a dynamic approach to balancing benefits and costs - Aveling, Emma-Louise; Roberts, Jane E.; Taylor, Lauren A.; Bhuiya, Nazmim; Singer, Sara J. (Frontiers in Health Services, 2023)
Efforts to address complex public health challenges can benefit from cross-sector collaboration, while also fostering growing business sector engagement in promoting health equity. What form business-nonprofit collaboration should take, however, is a difficult question for managers and leaders. Hybrid organizational forms, which combine for-profit and nonprofit elements within a single organization in unconventional ways, offer an innovative and potentially promising approach. Yet, while existing typologies of cross-sector collaboration have identified hybrid forms at one end of a continuum of possible forms of collaboration, these typologies do not differentiate the diversity such hybrid forms may take, and the costs and benefits of these innovative hybrid forms are poorly understood. This leaves managers interested in promoting public health through business-nonprofit hybrid organizing with limited guidance about how to maximize potential merits while mitigating drawbacks. We performed a qualitative comparative case study of three examples of business-nonprofit hybrid organizing. Data collection included 113 interviews with representatives from 42 organizations and observation of case study activities. We used thematic analysis within and across cases to characterize the form of hybrid organizing in each case and to examine benefits and costs of different forms for supporting initiatives. We identified two hybrid, collaborative forms – Appended and Blended forms. Each form had benefits and costs, the significance of which shifted over time contingent on changing strategic priorities and operating environments. No particular form of business-nonprofit hybrid organizing is inherently better than another. Benefits and costs of particular forms become more or less important for establishing and sustaining initiatives under different conditions, requiring a dynamic view. Optimizing hybrid organizing and ensuring resilient collaborations may mean allowing collaborative forms to evolve. Practitioners can manage tradeoffs between benefits and costs through an ongoing process of assessing the fit between a given collaborative form, strategic priorities, and relevant features of the operating environment. This dynamic view offers important insights for ensuring the resilience of business-nonprofit collaborative efforts to enhance public health.